DRY-MATTER INTAKE PER MOUTHFUL BY GRAZING DAIRY GOATS - PEINADOLUCENA, E; SANCHEZRODRIGUEZ, M; GOMEZCASTRO, A G; MATAMORENO, C; GALLEGOBARRERA, J A (SMALL RUMINANT RESEARCH, 1992)
Mouthful grass intake varied widely from season to season, with minimal values in winter (0.09 g DM) that increased to 0.51 g DM in Spring and decreased in Summer (0.21 g DM). Mouthful intake for shrubby species ranged between lowest for Cistus salvifolius (0.16-0.33 g DM) to C. ladanifer (0.95-3.57 g DM), followed by C. albidus (0.33-1.46 g DM). Quercus rotundifolia was the most frequently ingested arboreal species throughout the year, although the maximum DM content per mouthful (1.58 g) was for Olea europaea. These results show that the greatest weight per mouthful of grass was in spring. The largest amount of DM on a year-round basis was provided by the shrub (C. ladanifer, and the tree O. europaea. Differences in DM intake per mouthful for each species suggest that studies of comparative palatability based on grazing time or number of mouthfuls may lead to errors when estimating actual DM intake for different species studied. Such estimates should be corrected in the light of relative weight per mouthful for each food species.
APS
Keywords: Grazing; Olea europaea; Quercus rotundifolia